Tumour-associated macrophages (TAMs) in colon cancer and how to reeducate them - Yahaya, Muhamad Afiq Faisal; Mohd Lila, Mohd Azmi; Ismail, Saila; Zainol, Muhammad Faisal; Nik Abd. Rahman, Nik Mohd Afizan (Hindawi, 2019)
Tumour-associated macrophage (TAM) serves as the site in which most inflammatory cells coreside. It plays an important role in determining the progression and metastasis of a tumour. The characteristic of TAM is largely dependent on the stimuli present in its tumour microenvironment (TME). Under this environment, however, M2 macrophages are found to be in abundance compared to M1 macrophages which later promote tumour progression. Numerous studies have elucidated the relationship between TAM and the progression of tumour; hence, TAM has now been the subject of interest among researchers for anticancer therapy. This review discusses the role of TAM in colorectal cancer (CRC) and some of the potential candidates that could reeducate TAM to fight against CRC. It is with hope that this review will serve as the foundation in understanding TAM in CRC and helping other researchers to select the most suitable candidate to reeducate TAM that could assist in enhancing the tumouricidal activity of M1 macrophage and eventually repress the development of CRC.